Bioethics in primary health care and public health quality - Domínguez Márquez, Octaviano; Manrique Nava, Carolina (Acta Bioethica, 2011)
A review and transdisciplinary analysis study is carried out regarding the integration between total quality and health field processes, specifically in primary health care from a general medicine and public health perspective. Main issues of total quality and their focus on health care and the relevance of values, principles and school of thought objectively reflected in total quality processes are reviewed. Emphasis on total quality raises also the need to lead bioethical indicators to an objective condition and pose them as indispensable to complement quality indicators.